Exposure to anthropogenic areas may influence colonization by zoonotic microorganisms in scavenging birds - Wiemeyer, Guillermo Maria (2021)
Wild bird species have commonly been implicated as potential vectors of pathogens to other species, humans included. However, the habitat where birds live could influence the probability to acquire these pathogens. Here, we evaluated if the characteristics of the environment used by obligate scavenging birds (vultures) influence their colonization by zoonotic pathogens. For this, we particularly focused on Salmonella spp., a zoonotic pathogen commonly present in bird species. The occurrence of this bacteria was evaluated in free ranging Andean condors (Vultur gryphus) using natural environments from Argentina and compared with those obtained from condors under human care. In addition, we compared our results with those reported for other wild vultures using natural and anthropized environments at a global scale. We did not find Salmonella spp. in samples of wild condors. Captive condor samples presented Salmonella spp. with an occurrence of 2.8%, and one isolate of Meticilin Resistant Staphylococcus aureus, among other potential pathogenic microorganisms. Moreover, some species of free ranging vultures from diverse geographical areas using anthropized environments tend to present higher occurrences of Salmonella spp. These results highlight the importance of pristine ecosystems to protect vultures’ health toward pathogenic microorganisms that can produce disease in these birds, but also in other species. We call for more studies evaluating differences in occurrence of zoonotic pathogens in vultures according to the quality of the environment they use. Even when vultures have not been implicated in zoonotic pathogen spread, our results add information to evaluate potential events of pathogen spillover between vultures and from these birds to other species.